Pushko L. V. Descriptive potentiality of the nature words (in the English discourse) - Pushko L. V. (Philological Treatises, 2020)
This article explores the botanical nominations involved in the descriptions of people and examines the linguistic methods of cognitive representation of knowledge of the surrounding world in the human conceptual system with the help of these nominations